The Relationship between Spiritual Support and Quality of Life in the Elderly in Rukun Damai Village, Mahakam Ulu Regency - Yanto Rerungan; Edi Purwanto; Lukman Nulhakim (Formosa Journal of Science and Technology, 2023)
The purpose of this study was to determine the relationship between Spiritual Support and Quality of Life in the Elderly in Rukun Damai Village, Mahakam Ulu District. The research design is a descriptive correlation with a cross-sectional approach carried out in Rukun Damai Village, Mahakam Ulu Regency on 77 respondents. The sampling technique in this study was purposive sampling. The instruments used in the study were questionnaires for spiritual support, for the quality of life questionnaire from the WHOQOL BREF questionnaire. The results showed that the results of the Chi Square test yielded 0.001 (<0.05, H0 was rejected), meaning that there was a relationship between spiritual support and quality of life in the elderly in Kampung Rukun Damai, Mahakam Ulu District. There is a relationship between spiritual support and quality of life for the elderly in Rukun Damai Village, Mahakam Ulu Regency.